A luminescent metal–organic framework as an ideal chemosensor for nitroaromatic compounds. Issue 62 (8th August 2017) - He, Hongming; Chen, Si-Hang; Zhang, De-Yu; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : A 2D luminescent MOF serves as an ideal chemosensor for nitroaromatic compounds, especially for TNP, via luminescent quenching. Abstract : A luminescent two-dimensional metal–organic framework, [(Pr2 (TATMA)2 )·4DMF·4H2 O] n (1 ), was solvothermally synthesized based on the semi-rigid organic ligand 4, 4′, 4′′- s -triazine-1, 3, 5-triyltri- m -aminobenzoate (H3 TATMA).1 possesses binuclear {Pr2 (COO)6 } subunits and fully deprotonated TATMA 3− organic ligands, which can be further simplified into a 3, 6-connected kgd topology with the Schläfli symbol of (4 3 )2 (4 6 ·6 6 ·8 3 ). More importantly, 1 displays fast and reversible solid-state detection of nitroaromatic compounds, especially for TNP, via a luminescence response.